Accounting, analysis and audit in management of economic security expenditures - Deriy, Vasyl; Melnychuk, Inna (Herald of Economics, 2019)
Due to increasing globalization and competition, businesses have been forced to spend more time and money on taking measures aimed at economic security. Accounting, economic analysis, and audit play a significant role in the management of economic security expenditures since they make the management system more effective, reliable and sound. Therefore, this issue is currently of particular interest and needs to be interpreted. The purpose of the article is to examine the current state, challenges and future directions of improving accounting, economic analysis and audit in management of economic security expenditures.The methodology used for studying the issues relevant to economic security includes general and specific research methods enabling the description of economic processes, economic phenomena and facts, namely, those involving prime records, the registers of synthetic and analytical accounting, reports on economic security expenditures, carrying out analytical procedures, and auditing. The authors use monographic and graphic methods, methods of grouping and comparison of indicators, analysis of the dynamics and structure of expenditures, factor analysis, modelling and budgeting expenses on economic safety of enterprises, planning measures for the significant improvement of accounting, economic analysis and audit in enterprises.The authors claim that the term ‘accounting’ will exist until significant changes affect the objectives and contents of accounting. Although the Ukrainian word ‘бухгалтерський (book-keeping)’ is derived from the German word ‘Buch’ that means ‘book’, it is still in  use today. In the era of technological development, outdated paper books (accounting information carriers) are being replaced by electronic books which have become widespread. The article offers to improve accounting policies and procedures relevant    to measures aimed at economic security by separating information on synthetic account 92 “Administrative expenses” into nine sub-accounts: 921 “General corporate expenses”; 922 “Expenses on business trips and maintenance of management”; 923 “Expenses      on non-current tangible assets for general economic purposes”; 924 “Remuneration for advisory, information, audit and other services”; 925 “Communication and Internet costs”; 926 “Litigation settlement costs”; 927 “Taxes, fees (obligatory payments, licenses)”; 928 “Payment for services provided by commercial banks”; 929 “General-purpose expenses”. The following analytical accounts of the second, lower order should be opened to analytical account 9291 “Expenses on the economic safety of the enterprise”: 92911 “Costs of internal security service”; 92912 “Costs of data and commercial secrets protection”; 92913 “Costs of receiving, storing and transmitting technical and economic information”; 92914 “Costs of recruiting staff specialized in economic security”. The authors believe that in order to cover expenses on maintaining economic security it is advisable to reserve sources of funds   on synthetic account 47 “Provision of future costs and payments” by using sub-account 471 “Provision of other costs and payments” and analytical accounts to it: 4711 “Technical facilities for economic security”; 4712 “Use, maintenance and repair of facilities for maintaining economic security”; 4713 “Personnel support for economic security”. An audit of economic security expenditures is proposed to be carried out in relation to budgets for such expenditures, articles and elements, effectiveness and duration of economic security expenditures, etc. It is also necessary to analyze whether the dynamics and structure of costs are proportional to the budget for economic security of the enterprise. Furthermore, it is important to identify the main positive and negative factors that significantly affect such expenditures. Identifying factors like these allows experts to take certain measures that will partially or completely eliminate negative effects on economic security expenditures of the enterprise.Further research projects in accounting, economic analysis, audit, and analytical support for managing economic security expenditures of the enterprise should be based on the current national and foreign methodology and organization of accounting, economic analysis, and audit, analytical support of the operating activity of large and medium enterprises. Further studies should widely apply methods of operational and strategic planning, modelling cost-management systems, etc.